Calbindin D28k targets myo-inositol monophosphatase in spines and dendrites of cerebellar Purkinje neurons - Schmidt, Hartmut (National Academy of Sciences, 2005)
The Ca(2+)-binding protein calbindin D28k (CB) is vital for the normal function of the central nervous system but its specific functional role is largely unclear. CB is typically described as a mobile Ca(2+)buffer that shapes the spatiotemporal extent of cellular Ca(2+)signals. Recent biochemical data, however, indicate that CB also has characteristics of a Ca(2+) sensor and activates myo-inositol monophosphatase (IMPase), a key enzyme of the inositol-1,4,5-trisphosphate signaling cascade and an assumed target of mood-stabilizing drugs in the treatment of bipolar disorder. Here, we show that CB interacts with IMPase in cerebellar Purkinje neurons, a cell type well known to rely on inositol-1,4,5-trisphosphate-dependent synaptic integration. Quantification of the mobility of dye-labeled CB with two-photon fluorescence recovery after photobleaching revealed that a substantial fraction of CB is immobilized in spines and dendrites, but not in axons. Immobilization occurs over several seconds, is increased by suprathreshold synaptic activity, and can be relieved by a synthetic peptide that resembles the putative CB-binding site of IMPase, indicating that CB binds to immobilized IMPase. Measurements of the apparent diffusion coefficients of CB imply that CB does not interact with cytosolic IMPase or that the latter is present only in minute amounts in the spiny dendrites of Purkinje neurons. Our results suggest that CB acts as an activity-dependent sensor that targets membrane/cytoskeleton-bound IMPase in central neurons.